Konstytucjonalizm wobec „zemsty postmodernizmu” - Sulikowski, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The main purpose of this article is to discuss the current situation of constitutional discourse as a result of „Revenge of postmodernism”. This „Revenge” shows itself in taking over the methods of the leftist critique of democratic institutions by the radical right. This „Barbarization” of subtle methods of left-wing criticism leads to far-reaching consequences unforeseen by its founding fathers — Michel Foucault, Jacques Derrida or Judith Butler. The author, using various theories formulated by Chantal Mouffe, Ernesto Laclau and Artur Kozak, seeks to explain this phenomenon and to show its implications for the future evolution of the constitutional discourse
Keywords: konstytucjonalizm; postmodernizm